Republic of Armenia : Poverty Reduction Strategy Paper Progress Report-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory (JSA) Note examines the Poverty Reduction Strategy Paper (PRSP) Progress Report for Armenia. Overall, the Progress Report provides evidence of stronger-than-anticipated poverty reduction and economic performance, improvement in the labor market, and a number of other accomplishments, particularly in fiscal policy and social service delivery. The report also indicates that progress has been made on many issues raised in the previous JSA, including on improved monitoring and evaluation, participation, and aligning the budget process with the PRSP.